Does privacy matter to millennials? The case for personal cloud. Issue 1 (2nd January 2017) - Moqbel, Murad; Bartelt, Valerie; Al-Suqri, Mohammed; Al-Maskari, Azzah
ABSTRACT: To date, there is little research on the extent to which privacy, security, and trust influence consumer technology-use decisions based on generation. We, therefore, examine, through the lens of the expectancy-valence theory, the extent to which privacy, security, and trust influence the decision to use personal cloud computing among millennials. We also examine the moderating effect of innovativeness on these relationships. Our structural equation modeling (SEM) analysis of 371 millennials shows that privacy is irrelevant for millennials when making decisions to use personal cloud and that individuals with high innovativeness tend to disregard security when making an adoption decision.